Effectiveness of Social Marketing on Knowledge, Attitude and Practice on Child Nutrition by Women in South-West Nigeria (2011)
Despite intervention programmes aimed at improving child nutrition in Nigeria, the number of children with poor nutrition has consistently increased over the years. The usual top-down management approach to execution of intervention is contributory to this problem. Social marketing, a bottom-up and effective approach to intervention, has not been well studied in Nigeria. The effectiveness of social marketing on knowledge, attitude and practice of child nutrition by women in South-West Nigeria was therefore investigated. The study was carried out using quasi-experimental research approach and Focus Group Discussion (FGD). Two hundred and forty women were selected by systematic random sampling from ante-natal clinic in primary health centres in selected 10 local government areas in Oyo (4), Ekiti (3) and Osun state (3) based on probability proportionate sample to size with 90, 75, and 75 women interviewed from each of the states respectively. Data were collected from the two groups using structured questionnaire which included 50 points-knowledge, 17 points-practice and 5-points Likert-attitudinal scales before and after exposure to nutrition messages. In addition, one FGD each was conducted among women in each of the 10 LGAs. Fifty percent (experimental group) were exposed to nutrition messages for 12 weeks with emphasis on social marketing techniques, while the remaining served as control. Parameters assessed were women‟s personal characteristics, knowledge, attitude and practice with respect to child nutrition. Data were analysed using descriptive statistics, problem tree analysis, Pearson Product Moment Correlation, Chi square and t-test at p = 0.05. Mean age of women was 33 ± 7.7 years, 69.6% were married, mean household size was 5.10 ± 2.4 and mean number of children under-five was 2.90 ± 1.49. Half (50.4%) were educated and majority (67.5%) engaged in petty trading. The mean monthly income was N20, 330 ± 17,052. At baseline, information sources included radio (75.4%) and television (54.2%). Attitude to nutrition messages revealed favourable disposition to communication channels/promotion (53.8%), environment/ place (58.8%), nutrition messages/ product (53.0%) and abandonment of previous nutrition behavior/price (64.2%). The discussants stated that child nutrition was affected by income, cultural preference and nutritional knowledge. Post-intervention evaluation showed that the experimental group manifested an increase in knowledge from 50.4% to 90.2%, favourable attitude from 47.8% to 68.9% and nutrition practice from 58.3% to 75.5% when compared to increase in knowledge 50.6% to 57.2%, favourable attitude 48.6% to 50.4% and nutrition practice 49.7% to 52.8% of the control group. Marital status (χ2=16.94), family size (r = 0.26), education (χ2= 44.45), occupation (χ2=21.00), and communication channel (r = 0.23) were significantly related to nutrition behaviour. Knowledge was significantly different in Oyo (t = 2.93) and Ekiti (t = 2.29), while attitude was significantly different in Oyo (t = 4.23) and Osun (t = 3.99) before and after exposure to nutrition messages. Respondents exhibited significant difference in nutrition behavioural (t = 2.62) before and after the intervention. Social marketing using nutritional messages in audio, video and chart improved women‟s knowledge, attitude and practice of child nutrition. Adoption of the strategy for effective nutrition intervention programmes should be encouraged